SOCIAL CONSCIOUSNESS IN ART AND LITERATURE - Rai, Bhagwat Singh (International Journal of Research -GRANTHAALAYAH, 2026)
Art and literature are important aspects of human life as well as social life. With the development of civilization, humans first developed art for their expression and then, with intellectual development, also created literature. Thus, art and literature are the mediums responsible for human expression, which express a person's creative imagination and flights of mind and emotions. While art expresses beauty and ideas through visual display or music, literature creates stories, poems and dramas through words, which often influence each other and inspire human experience and civilization culture.